Pengembangan Media Pembelajaran E-Magazine Interaktif Berbasis Socio-Scientific Issue (SSI) pada Materi Ekologi dan Keanekaragaman Hayati Indonesia Kelas VII SMP - Siti Masitotul Mubarokah; Vindhy Dian Indah Pratika (Universitas Garut, 2026)
This study aimed to create an interactive e-magazine learning resource based on the Socio-Scientific Issues (SSI) approach, specifically covering ecology and biodiversity topics for 7th-grade junior high school students. Additionally, the study assessed the resource's validity and usability in an educational setting. This research employed the ADDIE development model, comprising five stages: analysis, design, development, implementation, and evaluation. The study involved three subject matter experts, three media experts, and 7th-grade students from SMP Negeri 1 Rejotangan. Data were collected using validation sheets for subject matter and media experts, as well as student response questionnaires, and were analyzed by calculating percentages. The results indicated that the e-magazine achieved a subject matter expert validation score of 83% (categorized as highly valid) and a media expert validation score of 86% (also highly valid), while the practicality rating based on student feedback reached 88% (categorized as highly practical). The innovation of this study lies in the creation of an interactive SSI-based e-magazine that integrates current environmental issues with content on ecology and Indonesian biodiversity for junior high school students. Consequently, the developed e-magazine is considered valid and practical for use as a science learning resource.Keywords: Ecology and Indonesian biodiversity, interactive e-magazine, socio-scientific issues (SSI)